Mesenteric vein thrombosis caused by secondary polycythaemia from AndroGel. (21st October 2014) - Katz, Heather; Popov, Eugene; Bray, Natasha; Berman, Barry
Abstract : Mesenteric vein thrombosis is a rare but potentially lethal cause of abdominal pain. It is usually caused by prothrombotic states that can either be hereditary or acquired. Testosterone supplementation causes an acquired prothrombotic state by promoting erythropoeisis thus causing a secondary polycythaemia. We report a case of a 59-year-old man with a history of chronic obstructive pulmonary disease (COPD) stage III, who presented with abdominal pain. Evaluation revealed an elevated haemoglobin and haematocrit, a superior mesenteric vein thrombosis on CT and a negative Janus kinase 2 mutation. The patient is currently being treated with 6 months of anticoagulation with rivaroxiban. Although a well-known side effect of testosterone is thrombosis, the present case is used to document in the literature the first case of mesenteric vein thrombosis due to secondary polycythaemia from Androgel in the setting of COPD.